Observations of two sprite‐producing storms in Colorado. Issue 16 (26th August 2016) - Lang, Timothy J.; Lyons, Walter A.; Cummer, Steven A.; Fuchs, Brody R.; Dolan, Brenda; Rutledge, Steven A.; Krehbiel, Paul; Rison, William; Stanley, Mark; Ashcraft, Thomas
Abstract: Two sprite‐producing thunderstorms were observed on 8 and 25 June 2012 in northeastern Colorado by a combination of low‐light cameras, a lightning mapping array, polarimetric and Doppler radars, the National Lightning Detection Network, and charge moment change measurements. The 8 June event evolved from a tornadic hailstorm to a larger multicellular system that produced 21 observed positive sprites in 2 h. The majority of sprites occurred during a lull in convective strength, as measured by total flash rate, flash energy, and radar echo volume. Mean flash area spiked multiple times during this period; however, total flash rates still exceeded 60 min −1, and portions of the storm featured a complex anomalous charge structure, with midlevel positive charge near −20°C. The storm produced predominantly positive cloud‐to‐ground lightning. All sprite‐parent flashes occurred on the northeastern flank of the storm, where strong westerly upper level flow was consistent with advection of charged precipitation away from convection, providing a pathway for stratiform lightning. The 25 June event was another multicellular hailstorm with an anomalous charge structure that produced 26 positive sprites in less than 1 h. The sprites again occurred during a convective lull, with relatively weaker reflectivity and lower total flash rate but relatively larger mean flash area. However, all sprite parents occurred in or near convection and tapped charge layers in adjacent anvil cloud. The results demonstrate the sprite production by convective ground strokes in anomalously charged storms and also indicate that sprite production and convective vigor are inversely related in mature storms. Key Points: Positive sprites were observed over anomalously electrified convection in Colorado Sprites did not occur until intense, mature convection began weakening Polarimetric and multi‐Doppler radar analyses indicated effects of storm microphysics and kinematics on sprite‐parent lightning